Ophiacantha aristata Koehler 1896 ... - Rodrigues, Clara F.; Paterson, Gordon L. J.; Cabrinovic, Andrew; Cunha, Marina R. (Zenodo, 2011)
Ophiacantha aristata Koehler 1896 (Fig. 2) Material examined. Captain Arutyunov MV, MSM01-03, stn 195, 1 ind. (DBUA 001063.01). Ecology and distribution. This is a bathyal North Atlantic species (822–1700 m) known from SW Ireland south to the Canary Islands (Paterson 1985). In the Gulf of Cadiz it was collected from a coral thicket (Dendrophylia cf. alternata, mostly dead branches with a few living polyps) at a single station at the flanks of Captain Arutyunov MV (1390 m) together with Ophiopristis gadensis sp. nov., Ophiactis abyssicola and Amphioplus hexabrachiatus. ... : Published as part of Rodrigues, Clara F., Paterson, Gordon L. J., Cabrinovic, Andrew & Cunha, Marina R., 2011, Deep-sea ophiuroids (Echinodermata: Ophiuroidea: Ophiurida) from the Gulf of Cadiz (NE Atlantic), pp. 1-26 in Zootaxa 2754 on page 7, DOI: 10.5281/zenodo.276727 ...